Modelling of powder consolidation using electro heating assisted by mechanical loading; Journal of Physics: Conference Series; Vol. 790, iss. 1 : Rheology and Modeling of Materials (IC-RMM2) - Knyazeva A. G. Anna Georgievna (2017, 2017)
Title screen